Booksellers and their catalogs in Hamidian Istanbul, 1884-1901 - Çetin, Sinan. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2010., 2010)
This study focuses on the role of booksellers' catalogs, namely Esamii Kütüb (Names of the Books), and in particular, of Kitabçı Arakel's catalog published in 1884, as a vehicle to promote the printed book as a commodity in the last quarter of nineteenth century Ottoman Istanbul. With the increase in the number, and the variety, of printed material in the Hamidian Era, booksellers proliferated in Istanbul, acting as the agents who defined themselves as a distinct branch of commercial enterprise only dealing with printed material, especially books in contrast to the still existing commercial as well as institutional activities organized around manuscripts. It argues that the booksellers' catalogs provide a basis for understanding and evaluating this emergent publishing industry centered in Istanbul and how this industry defined, categorized and in that sense ordered the printed book. This process also converged with the reform in the educational institutions of the Ottoman Empire and communicational infrastructure, which had a decisive influence on the activities of the bookshops. Booksellers tried to utilize the opportunities to expand their markets opened up by these reforms by way of catalogs. In addition, this thesis engages in a theoretical discussion of how metadata about the books available in the catalogs should be collected and represented as a way of providing a platform of evaluation in conjunction with the available modern bibliographies.
Keywords: Booksellers' catalogs -- Turkey.